Biological Analysis of the Kejen Shark (Carcharinus falciformis) at the Paotere Fish Landing Base - Risna Ramadani; Nuraeni L Rapi; Arnold Kabangnga (Indonesian Journal of Coastal and Marine Studies, 2025)
This study aims to analyze the biological aspects of the kejen shark (Carcharinus falciformis) landed at the Paotere Fish Landing Base (PPI), Makassar, including its size structure and growth pattern as a basis for information on sustainable resource management. The study was conducted in January–March 2025 using a field survey method. Kejen shark samples were obtained from fishermen's catches landed at the Paotere PPI. Each individual caught was measured for total length (cm) and body weight (kg). Data were analyzed to determine the size distribution and length–weight relationship using regression analysis. The results showed that the total length of male kejen sharks ranged from 65–145 cmTL and females 65–155 cmTL, with body weights of 1–13 kg and 1–25 kg, respectively. The length–weight relationship produced a regression equation with a coefficient of determination (R²) of 0.9061 and a growth coefficient (b) of 3.3188, indicating a positive allometric growth pattern. The size structure of the fish caught indicates that the catch encompasses a wide range of sizes, including sexually immature individuals. This situation has the potential to reduce the wild population of the kingfisher, given its relatively slow growth and reproduction rates, necessitating more selective and sustainable fishing management.